Blocked isocyanates: from analytical and experimental considerations to non-polyurethane applications. Issue 48 (14th November 2016) - Rolph, Marianne S.; Markowska, Anna L. J.; Warriner, Colin N.; O'Reilly, Rachel K.
Abstract : In this review we aim to provide an introductory guide to blocked isocyanates, through discussion on different examples of blocking groups, along with experimental considerations for their application. Abstract : In this review we aim to provide an introductory guide to blocked isocyanates, through discussion on different examples of blocking groups, along with experimental considerations for their application. The review brings together updated examples of functionalities used and places specific emphasis on the analytical techniques used for the determination of deblocking temperature, updating previous reviews with the newly applied technique of X-ray photoelectron spectroscopy (XPS). Additionally, we put forward a brief update on the use of blocked isocyanates for other non-traditional polyurethane based polymer applications. We also highlight the importance of matching the analytical technique to the application of the blocked isocyanate, with differences in material state and experimental parameters having a great impact on the deblocking temperature reported.